Kejadian perdarahan uterus abnormal di RSUP Prof. Dr. R. D. Kandou Manado tahun 2015 - Tendean, Genuine G.E.; Mewengkang, Maya; Wantania, John J.E. (Universitas Sam Ratulangi, 2016)
Abstract: Abnormal uterine bleeding (AUB) is the most frequent gynecologic symptoms in women of reproductive age outpatients with a prevalence of 11 of 13 women and is increasing with aging reaching 25% among women of reproductive age. This study was aimed to describe cases of AUB at Prof. Dr. R. D. Kandou Hospital Manado in 2015. This was a retrospective descriptive study using secondary data of the medical records. The results showed that there were 62 cases of AUB. Most of them were at the age of 41-50 years (33.87%) meanwhile the minimum were <20 years and 21-30 years (9.68%). Based on BMI, the highest percentage was BMI 23.0-24.9 (30%). For AUB classification PALM-COEIN, the majority were PUA-L (40%). Histological examination was performed in 30.76%. The most common treatment was medicated therapy and D & C (34.62%). Conclusion: In this study, the majority of AUB cases were aged 41-50 years, BMI of 23.0 to 24.9, and PALM-COEIN classification of PUA-L, and medicated therapy plus D & C. Keywords: prevalence, abnormal uterine bleedingÂ Abstrak: Perdarahan uterus abnormal (PUA) merupakan gejala ginekologik yang paling sering pada pasien rawat jalan wanita usia reproduksi dengan prevalensi 11 dari 13 wanita. Kejadian PUA meningkat dengan berjalannya usia, mencapai 25% pada wanita usia reproduksi. Penelitian ini bertujuan untuk mengetahui gambaran pasien PUA di RSUP. Prof. Dr. R. D. Kandou Manado tahun 2015. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data rekam medik. Hasil penelitian menunjukkan terdapat 62 data kasus PUA. Berdasarkan usia, terbanyak usia 41-50 tahun (33,87%) dan yang paling sedikit usia <20 tahun dan 21-30 tahun (9,68%). Berdasarkan IMT, IMT 23,0-24,9 yang paling tinggi (30%). Untuk klasifikasi PUA PALM-COEIN, terbanyak ialah PUA-L (40%). Pasien yang melakukan pemeriksaan histopatologik sebanyak 30,76% dan yang tidak melakukan pemeriksaan 69,24%. PUA dengan penanganan medikamentosa dan D&C memiliki persentase terttinggi (34,62%). Simpulan: Pada studi ini, kejadian PUA terbanyak pada usia 41-50 tahun, IMT 23,0-24,9, klasifikasi PUA-L, dengan pilihan penanganan terbanyak medikamentosa dan D&C.Kata kunci: kejadian, PUA